2010
DOI: 10.1063/1.3478202
|View full text |Cite
|
Sign up to set email alerts
|

Identification Of Molecular Structures Of Normal And Pathological Human Breast Tissue Using Synchrotron Radiation

Abstract: Scattering profiles of human breast tissues were measured by x-ray diffraction using a synchrotron radiation source in order to identify their structural features at molecular level (0.70≤q≤70.55nm -1 ). Several parameters were extracted from these scattering profiles and statistically assessed using discriminant analysis. From this analysis, only the ratio between the peak intensities at q=19.8nm -1 and at q=13.9nm -1 , as well as the FWHM were statistically significant and allowed distinguishing the human br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…1,2 X-ray diffraction (XRD) is a technology capable of detecting these changes through measuring the interference patterns of X-rays scattering off the molecular-scale structures. [3][4][5][6] While prior XRD measurement and analysis methods have proven useful for studying diseases, [7][8][9][10] they have typically been limited to analyzing only a few discrete locations at the surface of a prepared sample or specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 X-ray diffraction (XRD) is a technology capable of detecting these changes through measuring the interference patterns of X-rays scattering off the molecular-scale structures. [3][4][5][6] While prior XRD measurement and analysis methods have proven useful for studying diseases, [7][8][9][10] they have typically been limited to analyzing only a few discrete locations at the surface of a prepared sample or specimen.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] These imaging methods, including energy-dispersive and angular-dispersive raster scanning measurements, coherent scattering computed tomography, and coded aperture systems, seek to measure the XRD signatures of materials throughout a large field of view within reasonable scan times while maintaining adequate spatial resolutions for imaging applications. While simulation studies are often conducted for the design and optimization of these novel imaging architectures, [16][17][18][19] experimental validations on biologically relevant phantoms [20][21][22][23] and real biospecimens 3,6,8,13,15,24 have also occurred. These results have shown that tissues can be differentiated by spatially resolved XRD measurements; however, the resulting rich spatio-spectral datasets necessitate automatic data processing and classification techniques to parse the large data volume.…”
Section: Introductionmentioning
confidence: 99%
“…The carcinoma scatter peak is at 13 deg. 2,5,[7][8][9] The contrast between the tissue types is nearly doubled when using a system which utilizes the characteristic scatter rather than using attenuation imaging. 10 Differences are also seen in collagen alignment, which causes a diminishment of peaks at smaller momentum transfer values.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent scatter imaging is sensitive to disease at very early stages compared to conventional imaging. 2 Diffraction, which is the constructive interference of coherent scattered radiation, is highly dependent on a material's molecular structure. 3 Coherent scatter signals for tissues typically have been studied using a conventional diffraction measurement geometry.…”
Section: Introductionmentioning
confidence: 99%